Audience segmentation for campaign design: Addressing climate change in Singapore - DETENBER, Benjamin H. (Institutional Knowledge at Singapore Management University, 2016)
A nationally representative telephone survey (n = 1,006) was conducted to understand how different groups of Singaporeans regard the issue of climate change and their inclination toward action in dealing with it. We measured attitudes, knowledge, and perceptions of the problem of climate change and the role of various stakeholders in addressing it. The data were subjected to a latent class analysis to produce three distinctive segments of the population: the concerned, the disengaged, and the passive. These segments stand in contrast to those discovered in the United States, Australia, Germany, and India and suggest different strategies for public engagement campaigns. The results also clarify the need to account for national idiosyncrasies when promoting adaptation to, or mitigation of, climate change in different parts of the world.